Financial Inclusion as a Catalyst for Poverty Reduction in Nigeria (International Journal of Scientific Research and Management (IJSRM), 2018)
Financial inclusion which can be explained as access to formal financial services such as credit, savings and insurance opportunities is still very vague in developing countries such as Nigeria where there is high level of poverty. The country has a large number of ‘unbanked’ people whose business activities are not captured in the country’s economic reports. These ‘unbanked’ populaces are illiterates who are either unemployed or under-employed and lack access to financial services and information and are totally excluded in the financial ecosystem and market. Hence, this paper examines the role of financial inclusion in the reduction of poverty in Nigeria. It examines the roles of government and financial institutions and the use of various mobile initiatives such as mobile banking, mobile money, agent banking etc. as financial inclusion tools to stimulate poverty reduction. Time series analysis on data obtained from secondary sources between the periods of 1992 and 2016 was adopted and the paper covered financial inclusion as it relates to unbanked people in Nigeria. The paper found out that majority of the ‘unbanked’ in Nigeria are low income people who do not have access to financial services and information on financial inclusion. While few are timid on the need to use a bank, many them are willing to use banking services and believe the availability of these services will help improve their economic condition. The paper therefore recommends that the banks should be encouraged to continue to take advantage of all the financial inclusion policies of the government in mobilizing funds from the informal sector into the banking system. This can be best done by increasing the number of customers within the financial system as a tool for encouraging financial inclusion and stimulating the economy and thereby reducing poverty in the country.